Transparency in surgical randomized clinical trials: cross‐sectional observational study. Issue 5 (15th August 2020) - Helliwell, J. A.; Shelton, B.; Mahmood, H.; Blanco‐Colino, R.; Fitzgerald, J. E.; Harrison, E. M.; Bhangu, A.; Chapman, S. J.
Abstract : Background: RCTs provide the scientific basis upon which treatment decisions are made. To facilitate critical review, it is important that methods and results are reported transparently. The aim of this study was to explore transparency in surgical RCTs with respect to trial registration, disclosure of funding sources, declarations of investigator conflicts and data‐sharing. Methods: This was a cross‐sectional review of published surgical RCTs. Ten high‐impact journals were searched systematically for RCTs published in years 2009, 2012, 2015 and 2018. Four domains of transparency were explored: trial registration, disclosure of funding, disclosure of investigator conflicts, and a statement relating to data‐sharing. Results: Of 611 RCTs, 475 were eligible for analysis. Some 397 RCTs (83.6 per cent) were registered on a trial database, of which 190 (47·9 per cent) had been registered prospectively. Prospective registration increased over time (26 per cent in 2009, 33·0 per cent in 2012, 54 per cent in 2015, and 72·7 per cent in 2018). Funding disclosure was present in 55·0, 65·0, 69·4 and 75·4 per cent of manuscripts respectively. Conflict of interest disclosure was present in 49·5, 89·1, 94·6 and 98·3 per cent of manuscripts across the same time periods. Data‐sharing statements were present in only 15 RCTs (3·2 per cent), 11 of which were published in 2018. Conclusion: Trial registration, disclosure of funding and disclosure of investigator conflicts in surgical RCTs have improved markedly over the past 10 years. Disclosure of data‐sharing plans is exceptionally low. This may contribute to research waste and represents a target for improvement. Abstract : This cross‐sectional observational study explored transparency of surgical RCTs. It found that trial registration, presence of funding statements and disclosure of personal conflicts improved rapidly over the past 10 years. In contrast, disclosure of data‐sharing plans remains exceptionally low; this may contribute to research waste and represents an essential target for improvement. Standards improving but data sharing problematic. Abstract : Antecedentes: Los ensayos clínicos aleatorizados y controlados ( randomized controlled trials, RCT) proporcionan la base científica para la toma de decisiones terapéuticas. Es importante que los métodos y los resultados se presenten de forma transparente para facilitar la revisión crítica. El objetivo de este estudio fue investigar la transparencia en los RCTs del ámbito quirúrgico según su registro, declaraciones de las fuentes de financiación del estudio y conflicto de interés de los investigadores, así como información referente a compartir los datos. Métodos: Revisión transversal de RCTs quirúrgicos publicados. Se realizó una búsqueda sistemática de los RCTs publicados en 10 revistas de alto impacto en los años 2009, 2012, 2015 y 2018. Se exploraron cuatro dominios de transparencia: el registro de los ensayos, la declaración de los fondos utilizados, la declaración de los conflictos de los investigadores y la información referente a la forma de compartir los datos. Resultados: De 611 RCTs, se incluyeron en el análisis 475. Un total de 397 (83, 6%) estudios se registraron en una base de datos de ensayos clínicos, de forma prospectiva en 190 (47, 9%). El registro prospectivo aumentó a lo largo del tiempo (26, 0% en 2009, 33, 0% en 2012, 53, 5% en 2015 y 72, 7% en 2018). Se mencionaban las fuentes de financiación en el 55%, 65%, 69, 4% y 75, 4% de los manuscritos, respectivamente. La declaración de conflictos de interés estuvo presente en el 49, 5%, 89, 1%, 94, 6% y 98, 3% de los manuscritos en esos mismos períodos de tiempo. Las declaraciones relativas a compartir los datos de la investigación constaban en solo 15 (3, 2%) RCTs, 11 de los cuales fueron publicados en el 2018. Conclusión: En los últimos 10 años ha mejorado de forma notable el registro de los ensayos y las declaraciones de las fuentes de financiación y conflicto de interés en los RCTs quirúrgicos. La declaración referente a compartir los datos es excepcionalmente baja, lo que puede contribuir al desperdicio de la investigación y constituye un objetivo de mejora.